HH_14_7

# HH_14_7 - ( x-1) 4-( y-1) 4 x y z z = P 2 ( x, y ) FIGURE 3...

This preview shows pages 1–2. Sign up to view the full content.

(11/11/08) Math 10C. Lecture Examples. Section 14.7. Second-order partial derivatives Example 1 What are the second-order derivatives of f ( x , y ) = xy 2 + x 3 y 5 ? Answer: f xx = 6 xy 5 f xy = f yx = 2 y + 15 x 2 y 4 f yy = 2 x + 20 x 3 y 3 Example 2 Find the second-degree Taylor polynomial approximation of f ( x , y ) = 1 - cos x cos y at x = 0 , y = 0 . Answer: P 2 ( x, y ) = 1 2 x 2 + 1 2 y 2 (The graph of f ( x, y ) = 1 - cos x cos y is in Figure 1, and the graph of its Taylor polynomial approximation is the circular paraboloid shown in Figure 2 with the graph of f .) x y z z = 1 - cos x cos y x y z z = P 2 ( x, y ) FIGURE 1 FIGURE 2 Example 3 Figure 3 shows the graph of f ( x , y ) = 5 - x + y - ( x - 1 ) 4 - ( y - 1 ) 4 and Figure 25 shows the graph of f with the graph of its second-degree Taylor polynomial P 2 ( x , y ) at x = 1 , y = 1 . Give a formula for P 2 ( x , y ) . What type of surface is its graph? x y z z = 5 - x + y -

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ( x-1) 4-( y-1) 4 x y z z = P 2 ( x, y ) FIGURE 3 FIGURE 4 Answer: P 2 ( x, y ) = 5-x + y The graph of P 2 is a plane. Lecture notes to accompany Section 14.7 of Calculus by Hughes-Hallett et al. 1 Math 10C. Lecture Examples. (11/11/08) Section 14.7, p. 2 Example 4 Figure 5 shows the graph of f ( x , y ) = y 2-1 12 y 4-x , and Figure 6 shows its graph with the graph of its second-degree Taylor polynomial z = P 2 ( x , y ) at x = , y = . Give a formula for P 2 ( x , y ) . x y z z = y 2-1 12 y 4-x x y z z = P 2 ( x, y ) FIGURE 5 FIGURE 6 Answer: P 2 ( x, y ) = y 2-x...
View Full Document

## This note was uploaded on 09/30/2011 for the course MATH 10C taught by Professor Hohnhold during the Spring '07 term at UCSD.

### Page1 / 2

HH_14_7 - ( x-1) 4-( y-1) 4 x y z z = P 2 ( x, y ) FIGURE 3...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online